Redefining General Public Segment In Kustomfest: A Research On Visitor Motives In Attending A Kustom Kulture Festival - Wahyudi, Muhammad Emir Alhafeez; Dellyana, Dina (Integrasi Sains Media, 2024)
The Indonesian creative economy has experienced significant growth, with creative tourism emerging as a prominent driver. This study centers on Kustomfest, the Indonesian Kustom Kulture Festival, recognized as one of the largest Kustom Kulture hubs in the country. Between 2019 and 2023, there was a notable shift in the festival's audience composition, with the general public now constituting the majority segment. The research aims to identify and analyze the key motives driving the general public to attend Kustomfest, segment the market based on these motives, and examine each segment's sociodemographic profiles and behavioral characteristics. Three distinct market segments were identified, each motivated by different factors. Insights from this study can assist organizers of similar Kustom Kulture-related events in expanding creative tourism in Indonesia. By understanding visitor motivations and behaviors, event organizers can tailor marketing strategies, enhance visitor experiences, and capitalize on revenue opportunities from the general public segment. Recommendations are provided to attract, retain, and expand each segment through business model innovation, thus contributing to the sustained growth of Indonesia's creative economy. The findings highlight the importance of understanding visitor motivations and behaviors to maximize the impact of cultural events on the broader creative economy. These insights enable event organizers to foster growth in Indonesia's creative sector, ensuring that cultural festivals like Kustomfest continue to evolve and appeal to a diverse audience.